The application of heavy strength training in relative energy deficiency in sport - Hooper, D. R. (Journal of Science in Sport and Exercise, 2019)
A combination of high levels of physical activity, low sex hormone concentrations and subsequent low bone mineral density is commonplace in athletic populations. Low bone mineral density can lead to an increased risk of stress reactions or fractures, which can significantly reduce sport participation time. The use of heavy strength training has been effective at increasing bone mineral density in older, frail osteoporotic populations, and there is evidence that it would also be effective in athletic populations with low bone density. In addition to potentially reducing the risk of stress reactions and fractures, heavy strength training may be beneficial for endurance performance, including when being used as a replacement for some of the endurance activities. Thus, individuals exhibiting symptoms associated with the Female Athlete Triad, the Exercise Hypogondal Male Condition or Relative Energy Deficiency in Sports should consider implementing heavy strength training as part of their exercise regimen.